Association between initial ventilation mode and hospital outcomes for severe congenital diaphragmatic hernia - Wild, K. Taylor; Mathew, Leny; Ades, Anne M.; Rintoul, Natalie E.; Soorikian, Leane; Matthews, Kelle; Lee, Sura; Van Hoose, K. Taylor; Kesler, Erin; Flohr, Sabrina; Bostwick, Anna; Reynolds, Tom; et al. (Journal of perinatology, 2024)
Objective To determine the association between initial delivery room (DR) ventilator (conventional mechanical ventilation [CMV] versus high frequency oscillatory ventilation [HFOV] and hospital outcomes for infants with severe congenital diaphragmatic hernia (CDH). Study design Quasi-experimental design before/after introducing a clinical protocol promoting HFOV. The primary outcome was first blood gas parameters. Secondary outcomes included serial blood gas assessments, ECMO, survival, duration of ventilation, and length of hospitalization. Results First pH and CO 2 were more favorable in the HFOV group ( n = 75) than CMV group ( n = 85), median (interquartile range (IQR)) pH 7.18 (7.03, 7.24) vs. 7.05 (6.93, 7.17), adjusted p -value < 0.001; median CO 2 62.0 (46.0, 82.0) vs 85.9 (59.0, 103.0), adjusted p -value < 0.001. ECMO, survival, duration of ventilation, and length of hospitalization did not differ between groups in adjusted analysis. Conclusion Among infants with severe CDH, initial DR HFOV was associated with improved early gas exchange with no adverse differences in hospital outcomes.